فعالية طريقة البقائين والضالعين في ترقية مهارة الكتابة - Kholidia Yusuf (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2017)
في عملية تعلم اللغة العربية ، يجد الطلاب صعوبة في فهم مهارات الكتابة حتى تكون هناك حاجة إلى طريقة التعلم المناسبة. جرب الباحثون طريقة التعلم Two Stay Two Stray في تعلم مهارات الكتابة. طريقة TSTS هذه هي طريقة مشاركة الطلاب لمعرفتهم وخبراتهم مع المجموعات الأخرى. بهدف جعل عملية التعلم سهلة وممتعة. تتكون الطريقة التجريبية باستخدام المنهج الكمي مع التجربة شبه ، من مجموعتين ، هما المجموعة التجريبية والضابطة. أداة جمع البيانات: التوثيق والمراقبة والاختبار المسبق واختبار ما بعد الاختبار. كانت نتائج هذه الدراسة: (1) تعلم الكتابة بطريقة ثنائية الشيطان كان فعالاً مع نتيجة اختبار t التي أظهرت أن نتيجة الحساب t كانت 6.78 أكبر من t- جدول (جدول كبير) 1% = 2,39% و 5% = 1,67% ، وبالتالي فإن فرضية الباحث مقبولة.In the process of learning Arabic, students find it difficult to understand the writing skills so that appropriate learning method is needed. Researchers tried the Two Stay Two Stray learning method in learning writing skills. This TSTS method is the way students share their knowledge and experience with other groups. With the aim to make learning process easy and fun. The experimental method using quantitative approach with quasi experiment consists of 2 groups, namely experiment and control group. Instrument of data collection: documentation, observation, pre-test and post-test. The results of this study were: (1) writing learning with Two Stay Two Stray method was effective with the result of t-test that showed that the result of t arithmetic was 6.78 bigger than t-table (significant table) 1% = 2,39 and 5 % = 1.67, thus the researcher's hypothesis is acceptable.